(NdETI KAPITANA gRANTA(B: [(NrOMAN(B] / s - (NwERN(B, (Nv@LXs ((NaLMA(B-(NaTA(B: s (NvALYN(B, s, 1987)
(N{IROKO IZWESTNYJ ROMAN KLASSIKA FRANCUZSKOJ LITERATURY(B.s
rus
Keywords: (NpRIKL@^ENIQ(B, (NPUTE[ESTWIQs; (NpRIKL@^EN^ESKIJ ROMANs